Modulation of Hypoxia in Solid Tumor Microenvironment with MnO2 Nanoparticles to Enhance Photodynamic Therapy. (20th May 2016) - Zhu, Wenwen; Dong, Ziliang; Fu, Tingting; Liu, Jingjing; Chen, Qian; Li, Yonggang; Zhu, Ran; Xu, Ligeng; Liu, Zhuang
Abstract : Hypoxia not only promotes tumor metastasis but also strengthens tumor resistance to therapies that demand the involvement of oxygen, such as radiation therapy and photodynamic therapy (PDT). Herein, taking advantage of the high reactivity of manganese dioxide (MnO2 ) nanoparticles toward endogenous hydrogen peroxide (H2 O2 ) within the tumor microenvironment to generate O2, multifunctional chlorine e6 (Ce6) loaded MnO2 nanoparticles with surface polyethylene glycol (PEG) modification (Ce6@MnO2 ‐PEG) are formulated to achieve enhanced tumor‐specific PDT. In vitro studies under an oxygen‐deficient atmosphere uncover that Ce6@MnO2 ‐PEG nanoparticles could effectively enhance the efficacy of light‐induced PDT due to the increased intracellular O2 level benefited from the reaction between MnO2 and H2 O2, the latter of which is produced by cancer cells under the hypoxic condition. Owing to the efficient tumor homing of Ce6@MnO2 ‐PEG nanoparticles upon intravenous injection as revealed by T1‐weighted magnetic resonance imaging, the intratumoral hypoxia is alleviated to a great extent. Thus, in vivo PDT with Ce6@MnO2 ‐PEG nanoparticles even at a largely reduced dose offers remarkably improved therapeutic efficacy in inhibiting tumor growth compared to free Ce6. The results highlight the promise of modulating unfavorable tumor microenvironment with nanotechnology to overcome current limitations of cancer therapies. Abstract : Multifunctional chlorine e6 (Ce6)‐loaded MnO2 nanoparticles with surface polyethylene glycol (PEG) modification (Ce6@MnO2 ‐PEG) are formulated for T1‐weighted magnetic resonance imaging and enhanced tumor‐specific photodynamic therapy via regulating the intratumoral hypoxia. The results highlight the promise of modulating unfavorable tumor microenvironment with nanotechnology to overcome current limitations of cancer therapies.